Development and validation of the measurement tools and health education module on knowledge and practices for dengue among kindergarten children in Kelantan - Subramaniam, Neevaarthana (2023)
Dengue had been classified as one of the longest existing vector-borne diseases in Malaysia. Community members of all age groups had been prone to dengue infection, however, awareness related studies on dengue among kindergarten children aged five to six years had not been widely explored. Hence, this study aims to assess knowledge and practice levels and test the educational intervention programmes for young children in urban, sub-urban and rural areas of Kelantan. To achieve the objective, this study consisted of a cross-sectional and interventional study design which was conducted in four different phases. In Phase I, a guided interview-based questionnaire with 40 initial items to measure knowledge and practice levels was developed. Flashcards representing the illustration for selected items were also developed. The interview-based questionnaire was then validated and revised through content validity and face validity. The revised interview-based questionnaire was proceeded for item, factor and reliability analysis. The finalised interview-based questionnaire was then pre-tested following a cross-sectional study design among randomly selected 200 kindergarten children. In Phase II, a total of 396 kindergarten children were recruited to obtain knowledge and practice levels using the pre-validated interview-based questionnaire. Next, in Phase III, activity-based and module-based intervention programmes were developed, validated by experts and revised accordingly. In Phase IV, the revised activity and module intervention programmes were proceeded to be tested among 46 and 72 kindergarten children, respectively. Data from all the phases were analysed using the Statistical Package of the Social Sciences (SPSS) according to the respective tests needed to produce the results. For the outcome of this study, the final version of questionnaire consisted of 33 items, with a good internal consistency of Cronbach Alpha of 0.788. Through the measurement of knowledge and practice, practice levels were seen to be significantly higher in both urban and sub-urban areas compared to the rural area (p < 0.05). Significant differences (p < 0.001) were observed in both knowledge and practice scores among participants after implementation of educational intervention programmes. Therefore, this study concludes that the approach using the interview-based questionnaire and the specifically designed educational intervention programmes are effective. They can be considered valid and reliable study instruments for early exposure of dengue knowledge and practices among kindergarten children aged five to six years old.